SENI (RUPA) BALI HINDU DALAM PERSPEKTIF EPISTEMOLOGI BRAHMA WIDYA - IGP Sugandhi (Institut Seni Indonesia Surakarta, 2005)
Arts actually grew in the socio-culture and religious-magic of the community or nationâ€™s cultural system, as Islamic arts grew in the Arabic socio-culture and religious-magic in the Arabian Peninsula, and as primordial Christianity did in Jerusalem. In respect to this, the aim of this paper was to understand further about what, why and how Hindu Balinese (visual) arts were from a Hindu perspective. In other words, to discover which Hindu doctrines have influenced Hindu (visual) arts, in order to differentiate religious arts from profane or secular ones. By understanding the meaning of adagiums underlying the creative concept, it is hoped to discover the true Hindu (visual) arts. In order to discuss religious and non-religious arts, the study place emphasis on immanent and transcendent problems in reUgious and cultural life. The conclusionÂ 0!Â the study was that Hindu arts had two distinct characteristics: firstly, sacred Hindu arts, or arts that were directly related to religious rites and had an influnetial capacity; and secondly, secular Hindu arts, or arts that were not directly related to religious rites, and were therefore of a profane nature. Nevertheless, both were essentially dharma.Keyword: art, culture, religy